Why do cities in the global South pursue waste incineration rather than source segregation and recycling? Insights from Bangladesh - Akther, Shahana; Evans, James; Millington, Nate (Frontiers in Sustainability, 2024)
Introduction Source segregation and recycling of waste are crucial components of sustainable solid waste management. They receive little attention due to lack of political interest and institutional capacity, weak regulatory frameworks and enforcement, lack of economic incentives and low priority in planning. A complex economic system is involved in waste management in the global South, along with an informal sector that collects and recycles valuable materials. Rather than searching for solutions to improve collection and disposal services, this study uses a political ecology approach to understand how political economy influences and controls municipal solid waste management practices on the ground focusing on source segregation and recycling and how power relations influence how waste is handled, disposed of, and recycled. Dhaka’s waste governance regime emphasizes waste-to-energy generation without considering source segregation and recycling. Waste governance wants to benefit from informal waste collection and recycling without integrating them into policy frameworks, even though they have high resource recovery potential. The paper asks why, despite the potential to implement the 3R strategy by source segregation and promote sustainable waste management, the government opted for a centralized mechanical solution (incineration) for handling waste. Methods This study uses qualitative social research techniques to investigate a contemporary city-scale case study. The data collection techniques consisted of interviews with key stakeholders, focus group discussions, field observations and document reviews in Dhaka, Bangladesh between July and September 2022. Results The city authorities are interested in incineration technology due to the scarcity of land and the difficulty of obtaining it, while the existing dump sites are overflowing. Incineration technology can help city authorities avoid acquiring land by reducing their waste disposal footprint. City authorities perceive segregated waste collection as an additional burden because they lack the institutional and financial capacity to develop reliable separate waste collection systems. Additionally, high-level politicians have used images of incineration technologies to support modernist ideas about national development by emphasizing a centralized mechanical waste management system. On the other hand, international investors are interested in investing in technology and finance for incineration. In addition, city authorities believe composting and recycling on a small scale are not effective at managing the city’s large volumes of waste. It is likely that the new waste policy intervention (incineration) in Dhaka will lead to conflict over resources if city authorities do not properly recognize the existing waste infrastructures and informal recycling sector. Discussion Using the political ecology approach, the study examines why the government is less interested in implementing the 3R strategy (reduce, reuse, recycle) by segregating waste at the source level through the use of existing waste infrastructure rather than promoting centralized mechanical solutions. The city authorities are not interested in source segregation due to lack of institutional and financial capacity. The government needs to provide incentives for household source segregation and primary waste collection. City authorities are not interested in supporting incentives for source separation or waste recycling due to lack of financial capacity and political risk. Source segregation is essential for reducing waste volume and promoting sustainable resource recovery. Effective and sustainable waste management in the global South requires an integrated formal and informal approach to enhance source segregation and resource recovery. The study provides an evidence-based understanding of political ecology’s influence on MSW management practices, policy interventions and decision-making processes and offers insight into how to support effective 3R strategy implementation, facilitate policymaking, and contribute to additional knowledge for other megacities in the global South that face similar challenges.